2021
DOI: 10.1016/j.vas.2021.100169
|View full text |Cite
|
Sign up to set email alerts
|

Studies on heavy metals and fish health indicators in Malapterurus electricus from Lekki Lagoon, Lagos, Nigeria

Abstract: The aquatic ecosystem is constantly being disturbed by rising levels of different classes of pollutants of human origin in the form of urban, agricultural and industrial discharges. In this study, the health of fish Malapterurus electricus was examined, to serve as a reflection of the impact of anthropogenic disturbances in the Lekki lagoon. Eighty six samples of the fish were analysed for parasitic infections, heavy metals, microorganisms in their internal and external body parts while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…Fish liver damage due to heavy metal exposure has been reported in various geographical sites (Kuton et al 2021 ; Rubalingeswari et al 2021 ; Weber et al 2020 ; Kumar Maurya et al 2019 ; Łuczyńskaa et al 2018 ; Uysal 2011 ) indicating the importance of their monitoring and evaluation. Kumar Maurya et al ( 2019 ) revealed that heavy metal accumulation in fish tissues is in the magnitude order of liver > gill > muscle pointing out Ni, Cr, Pb, Cu, Cd, Zn, and Fe as dominant metals influencing toxicity in fish tissues (Rubalingeswari et al 2021 ).…”
Section: Wwtp-associated Legacy Contaminants and Emerging-concern Con...mentioning
confidence: 99%
“…Fish liver damage due to heavy metal exposure has been reported in various geographical sites (Kuton et al 2021 ; Rubalingeswari et al 2021 ; Weber et al 2020 ; Kumar Maurya et al 2019 ; Łuczyńskaa et al 2018 ; Uysal 2011 ) indicating the importance of their monitoring and evaluation. Kumar Maurya et al ( 2019 ) revealed that heavy metal accumulation in fish tissues is in the magnitude order of liver > gill > muscle pointing out Ni, Cr, Pb, Cu, Cd, Zn, and Fe as dominant metals influencing toxicity in fish tissues (Rubalingeswari et al 2021 ).…”
Section: Wwtp-associated Legacy Contaminants and Emerging-concern Con...mentioning
confidence: 99%
“…On the other hand, Kamaruzzaman et al (2010) [94] reported that the concentrations of Zn, Cu, and Pb follow the order stomach > muscle > gills in S. leptolepis, E. affinis, P. niger, L. malabaricus, E. sexfasciatus, R. kanagurta, N. japonicus, and M. cordylafrom from the Pahang coastal water in Malaysia. The concentrations of metals in several fish samples were found to be low [46,[95][96][97][98]. Copat et al (2013) [99] reported similarly low levels of Cd and Pb in shellfish samples from the eastern Mediterranean Sea.…”
Section: Metalsmentioning
confidence: 99%
“…Fish species has been used as bio-indicators in many research carried out on heavy metal pollution in the environment [8,9]. Fish is low in cholesterol and contains all essential amino acids and is estimated to provide roughly 60% of the world's protein requirements, with 60% of the developing world obtaining more than 30% of their animal protein from fish [10]. Heavy metals can build up in fish and proliferate throughout the food web, causing health problems in humans, such as cardiovascular, renal, and neurological disorders [11].…”
Section: Introductionmentioning
confidence: 99%